Substitution for lost one-hour means of the geomagnetic elements for the first half of the 20-th century at the Hurbanovo Geomagnetic Observatory by means of neural networks - VALACH, Fridrich; VÁCZYOVÁ, Magdaléna; DOLINSKÝ, Peter; VAJKAI, Melinda (Contributions to Geophysics and Geodesy, 2013)
The existence of long-acting observatories by itself does not guarantee that their historical magnetograms are available or complete. In the archive of the Hurbanovo Geomagnetic Observatory (acronym HRB; geographical coordinates 47.86° N, 18.19° E), records of the geomagnetic field made on photo paper covering the period between the two World Wars were found for which the values of the baselines are unknown. We studied if a feed-forward neural network with one hidden layer can be used to supplement one-hour means of the geomagnetic elements D, H and Z of observatory HRB, using for this purpose the geomagnetic data of observatories Potsdam, Seddin and Niemegk (all of them being referenced to Niemegk). We focused our interest on the first half of the 20-th century. The neural-network model for element D proved to be applicable to substitute for the lost data of the magnetic declination at observatory HRB; however, the usability of the model for both elements H and Z turned out to be limited to a few years close to beginning or end of data gaps. Further we supplemented the time series of annual means of geomagnetic elements D, H and Z at observatory HRB with the model data.